PERAN LEMBAGA DAKWAH DALAM MENGEMBANGKAN POTENSI MAHASISWA DI JURUSAN MANAJEMEN DAKWAH - Nurul Fadilah Fadilah (UIN Mataram, 2022)
This research aims to find out the role of da'wah institutions in developing the potential of da'wah management students, besides that this research aims to find out how these da'wah institutions can change da'wah management students to be able to think more critically, intelligently with a personality of faith and piety. This research is motivated by the role of da'wah institutions that are less than optimal in influencing and changing students of da'wah management. This research uses a type of qualitative research with a descriptive approach, in which researchers use interview techniques to collect relevant data, the interviews used are online interviews. The researcher gave questions to UIN Mataram students majoring in Da'wah Management.